2003
DOI: 10.1210/en.2003-0035
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Estrogen Down-Regulates Prostatic Androgen Receptor through a Proteosome-Mediated Protein Degradation Pathway

Abstract: Brief exposure of male rats to estrogens during the neonatal period interrupts normal prostate development, alters epithelial cell differentiation, and predisposes this gland to hyperplasia and severe dysplasia analogous to prostatic intraepithelial neoplasia (PIN) with aging. Previous work demonstrated that the reduced growth, secretory activity, and androgen sensitivity that are observed in the adult ventral lobe are a function of reduced androgen receptor (AR) levels. Down-regulation of AR protein was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
4

Year Published

2004
2004
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 49 publications
2
55
1
4
Order By: Relevance
“…These data indicate that the mechanism underlying AR regulation by androgens involves differential transcriptional and/or post-transcriptional events, which will likely be cell-and tissue-specific (Yeap et al 1999). In this sense, recent findings in the prostate gland showed that AR is down-regulated by androgen withdrawal as well as estrogen treatment, through a post-transcriptional pathway mediated by proteasome (Woodham et al 2003). In the present study, ligation of the efferent ductule did not affect levels of immunodetectable AR, nor did unilateral castration.…”
Section: Discussionmentioning
confidence: 80%
“…These data indicate that the mechanism underlying AR regulation by androgens involves differential transcriptional and/or post-transcriptional events, which will likely be cell-and tissue-specific (Yeap et al 1999). In this sense, recent findings in the prostate gland showed that AR is down-regulated by androgen withdrawal as well as estrogen treatment, through a post-transcriptional pathway mediated by proteasome (Woodham et al 2003). In the present study, ligation of the efferent ductule did not affect levels of immunodetectable AR, nor did unilateral castration.…”
Section: Discussionmentioning
confidence: 80%
“…It was observed in early studies that the activational response to androgens during adulthood is permanently blunted in estrogenized rats (46) and we determined that this effect is mediated, in part, through an immediate and permanent reduction in prostatic AR expression (15,48,58,59). Furthermore, the temporal expression patterns and quantitative levels of several other members of the steroid receptor superfamily are dysregulated by early exposure to high doses of estradiol.…”
Section: Molecular Pathways For Developmental Estrogenization Of the mentioning
confidence: 83%
“…Additionally, neonatal estrogen exposure downregulates androgen receptor level in male reproductive organs (Prins & Birch 1995, Woodham et al 2003 and lowers plasma testosterone (Sharpe et al 1998, Atanassova et al 2000. Testosterone coadministration with estrogen mitigates developmental abnormalities affecting the male reproductive tract (Rivas et al 2003).…”
Section: Discussionmentioning
confidence: 99%